THE ANXIETY OF MAJOR CHARACTER IN JOHN STEINBECK'S THE RED PONY: A PSYCHOANALYTIC APPROACH - WIDYAYANTI , RITA (2007)
This study concerns with the novel entitled The Red Pony, which is written by John Steinbeck's. The analysis of this research paper is focused on how the major character's anxiety is reflected in the major character, namely, Jody Tiflin based on its structural elements and psychoanalytic approach. In analyzing the novel, the writer applies the theory of psychoanalysis by Sigmund Freud. This research belongs to qualitative research, which employs textual data. The textual data are taken from two sources namely the novel itself as primary data sources and other materials which are related to the study as secondary data source. Based on the analysis, the researcher draws some conclusions. Firstly, the novel John Steinbeck's was created based on Steinbeck's autobiography. Secondary, John Steinbeck's shows the conflict in the family that influences Jody Tiflin in getting his anxiety. Third, through his creation of character and characterization, setting, plot and theme. The novel gives a clear description that anxiety experiences by Jody Tiflin causes her to do something carefully.